Modular synthesis of dihydroxyacetone monoalkyl ethers and isosteric 1-hydroxy-2-alkanones - Gueclue, Deniz; Rale, Madhura; Fessner, Wolf-Dieter (European Journal of Organic Chemistry, 2015)
Straightforward methods for the efficient, systematic preparation of libraries of the title compound classes have been evaluated. A general and efficient modular route to dihydroxyacetone monoethers was developed based on trityl glycidol, which, through epoxide opening, oxidation, and deprotection, provided variously alkylated ethers by three routine operations in good overall yields (eight examples, 24-59%). The preparation of structurally related 1-hydroxyalkanones depends on the availability of the most economic starting materials and on their physicochemical properties. Thus, the most practical one-step approaches consisted of the sec-selective oxidation of short-chain 1,2-diols (<= C-6) using NaOCl, and the direct ketohydroxylation of 1-alkenes (>= C-6) using buffered stoichiometric KMnO4 or catalytic RuO4 with reoxidation by oxone, for which mostly good overall yields were achieved on a multigram scale (nine examples, 15-78%).
Keywords: Alkylation; Hydroxylation; Ketones; Oxidation; Oxygenation; Regioselectivity; synthetic methods